Results of Chilean universities in international sustainability rankings; Resultados de las universidades chilenas en los rankings internacionales sobre sostenibilidad - Abello-Romero, J (Universidad del Zulia, 2025)
Sustainable development has emerged as a guiding principle for universities, driving their transformation in areas such as teaching, research, institutional management, and community engagement. Within this framework, international sustainability rankings—QS Sustainability Rankings, UI GreenMetric, and THE Impact Rankings—have established themselves as tools for evaluating and highlighting institutional commitment to this issue. This article aims to analyze results of Chilean universities in these three rankings, identifying positioning patterns and comparative trajectories. To this end, a descriptive-comparative documentary study is developed, based on secondary data available until 2025. The results show growing, albeit uneven, participation, with a greater presence and better relative performance by non-state universities belonging to the Council of Rectors of Chilean Universities. The Pontificia Universidad Católica de Chile stands out as the national leader, followed by institutions such as Universidad Andrés Bello, the Universidad de Concepción, and the Universidad del Desarrollo. In conclusion, it is noted that, despite significant progress, challenges in environmental sustainability persist. It is suggested that the research be expanded to include qualitative, longitudinal studies that incorporate institutional perceptions and actions. © Licencia de Creative Commons Atribución 4.0 Internacional (CC BY 4.0) https://creativecommons.org/licenses/by/4.0/deed.es